2018
DOI: 10.1044/2018_jslhr-l-17-0336
|View full text |Cite
|
Sign up to set email alerts
|

Children With Dyslexia Benefit From Orthographic Facilitation During Spoken Word Learning

Abstract: We demonstrate for the first time that children with dyslexia benefit from orthographic facilitation during spoken word learning. These findings have direct implications for teaching spoken vocabulary to children with dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 57 publications
0
39
0
1
Order By: Relevance
“…Of the 23 studies, 11 contained measures of orthographic, phonological and semantic learning (Chambre, Ehri & Ness, 2017;Han & Choi, 2016;Jubenville et al, 2014;Lucas & Norbury, 2014;Miles et al, 2016;Ricketts et al, 2009;Ricketts et al, 2015;Rosenthal & Ehri, 2008;Valentini, Ricketts, Pye & Houston-Price, 2018); three contained measures of semantic and phonological learning (Baron et al, 2018;Hu, 2008;Li et al, 2016); two contained measures of semantic and orthographic learning (Savaiano et al, 2015, Vadasy & Sanders, 2015 and one measured semantic learning To see or not to see / 11 only (Reitsma et al, 1983). The remaining six studies contained measures of only phonological learning (Ehri & Wilce, 1979;Mengoni et al, 2013;Saletta et al, 2016a;Saletta et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 23 studies, 11 contained measures of orthographic, phonological and semantic learning (Chambre, Ehri & Ness, 2017;Han & Choi, 2016;Jubenville et al, 2014;Lucas & Norbury, 2014;Miles et al, 2016;Ricketts et al, 2009;Ricketts et al, 2015;Rosenthal & Ehri, 2008;Valentini, Ricketts, Pye & Houston-Price, 2018); three contained measures of semantic and phonological learning (Baron et al, 2018;Hu, 2008;Li et al, 2016); two contained measures of semantic and orthographic learning (Savaiano et al, 2015, Vadasy & Sanders, 2015 and one measured semantic learning To see or not to see / 11 only (Reitsma et al, 1983). The remaining six studies contained measures of only phonological learning (Ehri & Wilce, 1979;Mengoni et al, 2013;Saletta et al, 2016a;Saletta et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…These ranged from teaching simple associations between pictures and labels (e.g., Baron et al, 2018;Ricketts et al, 2009) to exposing children to words in the context of meaningful stories (e.g., Vadasy & Sanders, 2015;Valentini et al, 2018). This demonstrates that orthographic facilitation for semantic learning can occur in a variety of learning situations.…”
Section: Semantic Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Baron et al. () found that children with dyslexia could learn and remember spoken words more accurately when the spoken and written forms of words were taught simultaneously.…”
Section: What Teachers Can Domentioning
confidence: 99%